Kinetics, detergent compatibility and feather-degrading capability of alkaline protease from Bacillus subtilis AKAL7 and Exiguobacterium indicum AKAL11 produced with fermentation of organic municipal solid wastes. Issue 11 (14th July 2020) - Emon, Tanvir Hossain; Hakim, Al; Chakraborthy, Diptha; Bhuyan, Farhana Rumzum; Iqbal, Asif; Hasan, Mahmudul; Aunkor, Toasin Hossain; Azad, Abul Kalam
Abstract: Alkaline proteases having activity and stability at alkaline pH possess a large variety of applications in many industries. Growing renewed interest urges the need to find a single alkaline protease with promising properties to be used in different industrial processes. Herein, alkaline proteases produced through fermentation of cheap and easily available organic municipal solid wastes by Bacillus subtilis AKAL7 and Exiguobacterium indicum AKAL11 were purified to investigate their kinetic and thermodynamic parameters, detergent compatibility, dehairing and feather-degrading capability. Sodium dodecyl sulfate polyacrylamide gel electrophoresis revealed that the purified protease from B. subtilis and E. indicum had molecular mass of ∼45 and 75 kDa, respectively. The protease from B. subtilis and E. indicum showed highest activity at 55 and 50 °C having low K m 1.17 and 0.567 mg/mL and high V max 416.67 and 333.33 µmole/min, respectively. The activation energy and temperature quotient of protease from B. subtilis and E. indicum were 26.52 and 65.75 kJ/mole, and 1.0004 and 1.0003 at 20–55 and 20–50 °C, respectively. Thermodynamics analysis revealed the formation of more ordered enzyme–substrate complexes along with spontenity of enzyme reaction. The protease from E. indicum exhibited better compatibility at higher concentration of detergents compared to that from B. subtilis. However, both proteases could retain more than 80% of the activity in the presence of 0.1% commercial laundry detergents. The purified protease from the both sources could degrade almost 90% of barbs and 40% of dry weight of the native feather and that from E. indicum could dehair cow skin. Results reported herein suggest that the alkaline protease from B. subtilis AKAL7 and E. indicum AKAL11 has biotechnological implications in detergent, leather and poultry feather processing industries.